2012
DOI: 10.1016/j.jmb.2012.05.006
|View full text |Cite
|
Sign up to set email alerts
|

Lateral Clustering of TLR3:dsRNA Signaling Units Revealed by TLR3ecd:3Fabs Quaternary Structure

Abstract: Toll-like receptor 3 (TLR3) recognizes dsRNA and initiates an innate immune response through the formation of a signaling unit (SU) composed of one double-stranded RNA (dsRNA) and two TLR3 molecules. We report the crystal structure of human TLR3 ectodomain (TLR3ecd) in a quaternary complex with three neutralizing Fab fragments. Fab15 binds an epitope that overlaps the C-terminal dsRNA binding site and, in biochemical assays, blocks the interaction of TLR3ecd with dsRNA, thus directly antagonizing TLR3 signalin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
32
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 40 publications
3
32
0
Order By: Relevance
“…The present work proposes a key for future analysis about an IFN-inducing signaling complex in the context of TLR4-mediated LPS signaling. Recent studies showed the importance of lateral TLR3 clustering mediated by TICAM-1 for downstream signaling (36), consistent with our model.…”
Section: Discussionsupporting
confidence: 92%
“…The present work proposes a key for future analysis about an IFN-inducing signaling complex in the context of TLR4-mediated LPS signaling. Recent studies showed the importance of lateral TLR3 clustering mediated by TICAM-1 for downstream signaling (36), consistent with our model.…”
Section: Discussionsupporting
confidence: 92%
“…These observations suggest that clustering of more than one TLR3 dimer may be necessary for an adequate immune response. A recent study supports this model . They produced antibodies that can block activity of TLR3.…”
Section: Dimerization and Activation Of Tlrsmentioning
confidence: 77%
“…B ). This kind of higher order clustering of receptor multimers has been proposed for quite a few membrane receptors . However, characterization of high‐resolution structures of the clusters has not been possible, mostly due to difficulties in making full‐length receptors and reconstituting complete signaling complexes in a membrane environment.…”
Section: Dimerization and Activation Of Tlrsmentioning
confidence: 99%
“…It has recently been shown that TLR3 is able to recognized long double-stranded RNA through lateral clustering of TLR3 units along the length of the dsRNA ligand [54]. Fibril recognition by TLR2 could occur in a similar way along the fibril.…”
Section: Discussionmentioning
confidence: 99%